2011
DOI: 10.3892/or.2011.1485
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induces epithelial-mesenchymal transition in colorectal cancer cells

Abstract: Abstract. Radiotherapy remains a major approach to adjuvant therapy for patients with advanced rectal cancer. Nevertheless, the effects of radiation on malignant processes have yet to be clarified. The aim of this study was to assess the biological effects of radiation on colorectal cancer (CRC) cells with special reference to epithelial-mesenchymal transition (EMT), a key developmental program often activated during cancer invasion and metastasis. We investigated the effect of radiation on two colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 23 publications
6
85
0
Order By: Relevance
“…[40][41][42][43][44][45][46][47][48][49][50][51][52] Ionizing radiation can promote traits of EMT in normal human mammary epithelium, 41 lung carcinoma 42,43 and colorectal cancer cells. 44 Furthermore, besides their role in E-cadherin repression, 45,46 Slug and Snail have been implicated in radioresistance-associated EMT. 47,48 Snail enhances resistance to apoptosis by activating the PI3K/Akt and Erk1/2 pathways, 28 consistent with our data showing increased radiosensitivity after inhibition of PI3K/Atk and Erk1/2 and downregulation of Snail.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44][45][46][47][48][49][50][51][52] Ionizing radiation can promote traits of EMT in normal human mammary epithelium, 41 lung carcinoma 42,43 and colorectal cancer cells. 44 Furthermore, besides their role in E-cadherin repression, 45,46 Slug and Snail have been implicated in radioresistance-associated EMT. 47,48 Snail enhances resistance to apoptosis by activating the PI3K/Akt and Erk1/2 pathways, 28 consistent with our data showing increased radiosensitivity after inhibition of PI3K/Atk and Erk1/2 and downregulation of Snail.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using colorectal cell lines have shown that expression of EMT inducers Snail1 or TGF-b in SMAD4-null cells increased resistance to chemotherapy (Hoshino et al 2009;Papageorgis et al 2011). Conversely, colorectal cell lines that were rendered oxaliplatin-resistant showed phenotypic and gene expression changes consistent with EMT (Yang et al 2006;Kawamoto et al 2012). Interestingly, tumor specimens taken from patients who had received 1 wk of preoperative chemotherapy prior to surgery resection displayed a more mesenchymal gene signature compared with prechemotherapy biopsy samples.…”
Section: Emt and Drug Resistancementioning
confidence: 99%
“…Interestingly, tumor specimens taken from patients who had received 1 wk of preoperative chemotherapy prior to surgery resection displayed a more mesenchymal gene signature compared with prechemotherapy biopsy samples. Furthermore, recurrent tumors frequently exhibited an EMT gene signature (e.g., decreased E-cadherin and increased vimentin) (Kawamoto et al 2012). Shintani et al (2011) found that, in non-small-cell lung carcinoma (NSCLC) patients, tumor biopsy prior to chemotherapy treatment showed epithelial markers but that this phenotype shifted toward mesenchymal markers following treatment.…”
Section: Emt and Drug Resistancementioning
confidence: 99%
“…During cancer progression, tumor cells become more invasive after undergoing EMT and gain access to blood vessels through intravasation resulting in distant metastasis, the major cause of death from cancer (22). Several factors have been shown to induce EMT in vitro and in vivo, including hypoxia, reactive oxygen species, transforming growth factor ␤1, and radiation (23)(24)(25). Radiation elicits cell behaviors that are strongly associated with epithelial cancer such as differentiation dysregulation, genomic instability, phenotypic transition such as EMT, and aberrant multicellular organization (26,27).…”
mentioning
confidence: 99%